Synergistic effect of O2-Cl− on localized corrosion failure of L245N pipeline in CO2-O2-Cl− environment. (August 2022) - Leng, Jihui; Frank Cheng, Y.; Liao, Kexi; Huang, Yuanjie; Zhou, Feilong; Zhao, Shuai; Liu, Xin; Zou, Qing
Highlights: Compared with Cl −, O2 was the main factor inducing localized corrosion. Synergistic effect of O2 -Cl − promoted the development of localized corrosion. Low Cl − contents (0 mg/L–3000 mg/L) promoted the expansion of localized corrosion. High Cl − contents (3000 mg/L–5000 mg/L) inhibited the cathodic process. Abstract: To enhance the understanding of the corrosion mechanism on rapid perforation failure, the corrosion behavior of L245N with the synergistic effect of O2 -Cl − and different Cl − contents in CO2 -O2 -Cl − environment were studied by weight-loss test and characterization analysis. It showed that the O2 was the dominant factor inducing localized corrosion and the synergistic effect of O2 -Cl − in CO2 -O2 -Cl − environment mainly accounted for the growth of the corrosion, because porous Fe oxides generated by O2 promoted the mass transfer and catalysis of Cl − and Cl − in turn promoted the expansion of localized corrosion pits. The increase of the Cl − under low content enhanced the synergistic effect with O2, while high content of Cl − (3000–5000 mg/L) could reduce the solubility of CO2 /O2 and replace the adsorption of corrosive medium and ions on the substrate surface, inhibiting the cathodic process of corrosion reaction.